2016
DOI: 10.1111/inm.12284
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of involuntary transport under mental health legislation

Abstract: Police have historically been responsible for transporting people during a mental health crisis in Australia. A major change to the New South Wales (NSW) Mental Health Act (MHA) in 2007 expanded the range of coercive transportation agencies to include NSW Ambulance (paramedics) and NSW Health (mental health nurses). Anecdotal reports, however, describe a lack of clarity around how these changes should be implemented in practice. This research aims to explore this lack of clarity through qualitative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…17 Of these, 50 focused on the experiences of solely patients and 6 focused on the experiences of both patients and carers. In total, 30 studies were conducted in the UK (including England and Scotland), 11,1846 9 in Sweden, 13,4754 5 in Australia, 5559 5 in Ireland, 6064 2 in Norway, 65,66 and a study each were identified from Austria, 67 Finland, 68 Greece, 14 Israel 12 and the USA. 69 All papers identified were reported in the English language.…”
Section: Resultsmentioning
confidence: 99%
“…17 Of these, 50 focused on the experiences of solely patients and 6 focused on the experiences of both patients and carers. In total, 30 studies were conducted in the UK (including England and Scotland), 11,1846 9 in Sweden, 13,4754 5 in Australia, 5559 5 in Ireland, 6064 2 in Norway, 65,66 and a study each were identified from Austria, 67 Finland, 68 Greece, 14 Israel 12 and the USA. 69 All papers identified were reported in the English language.…”
Section: Resultsmentioning
confidence: 99%
“…This emotional bond with a person with a mental disorder has also been shown in research in other countries, such as with police officers in the United Kingdom (UK), where they express the desire to help and to have empathy and understanding of people with mental disorders (25). A gentle communicative style is required to gain trust, rapport and compliance from the person under compulsory admission (37). The strategy of using dialogue and giving time to patients to explain themselves is perceived by people with a serious mental disorder as a more humane treatment (38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of using dialogue and giving time to patients to explain themselves is perceived by people with a serious mental disorder as a more humane treatment (38, 39). For patients, being treated as humans is crucial to perceive the interaction as positive and for that, factors, such as communication style, being listened to, gentle handling, putting them at ease and not rushing things are key (37, 39). This procedural justice activity framework is crucial for the patient's cooperation and influences perceptions of police legitimacy.…”
Section: Discussionmentioning
confidence: 99%
“…1, 26 23 papers were selected: 12,16, 16 reported on the experiences of carers only, 12,16,[34][35][36][37][38][39][40][41][42][43][44][45][46][47] while seven reported on the experiences of patients, carers and other stakeholders. [27][28][29][30][31][32][33] Study characteristics are summarised in supplementary Table 1 including quality appraisal results that show that 20 of the 23 papers were rated as high-quality studies. Where studies were marked down during quality appraisal, this was often because of studies not having explicitly addressed the relationship between the researcher/s and participants (n = 19).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twelve papers reported on studies conducted in the UK (6 in England, 16,29,30,32,34,35 1 in Wales, 36 2 in Northern Ireland, 28,31 1 in Scotland, 12 and 2 not specified 37,38 ), with the remaining studies conducted elsewhere in Europe (Germany, 39,40 Greece, 41 Norway, [42][43][44] and the Republic of Ireland 33 ), Canada, 45 the USA 46 and Australia. 27,47 Although most studies reported on detention in general psychiatric hospitals, three papersall conducted in the UKreported on carers' experiences of assessment and treatment units and forensic services. [36][37][38] At least 260 carers were included in the reviewed studies.…”
Section: Study Characteristicsmentioning
confidence: 99%